Obesity and nonalcoholic fatty liver disease: current perspectives - Sarwar R (Dove Medical Press, 2018)
Raiya Sarwar,1 Nicholas Pierce,2 Sean Koppe3 1Department of Internal Medicine, University of Illinois at Urbana-Champaign, Champaign, IL, USA; 2University of Medicine and Health Sciences, New York, NY, USA; 3Department of Medicine, Division of Gastroenterology and Hepatology, University of Illinois at Chicago, Chicago, IL, USA Abstract: Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the most common cause of chronic liver disease due to an increase in the prevalence of obesity. The development of NASH leads to an increase in morbidity and mortality. While the first line of treatment is lifestyle modifications, including dietary changes and increased physical activity, there are no approved pharmacological treatment agents for NAFLD and NASH currently. Due to its complex pathophysiology, different pathways are under investigation for drug development with the focus on metabolic pathways, inflammation, and slowing or reversing fibrosis. There are several agents advancing in clinical trials, and promising results have been seen with drugs that affect hepatic steatosis, inflammation, and fibrosis. This review will provide an overview on NAFLD and some of the mechanisms of disease that are being targeted with pharmacologic agents. Keywords: nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, pharmacotherapy, clinical trials, antifibrotics